2009
DOI: 10.1259/bjr/89518905
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast-enhanced MRI for prostate cancer localization

Abstract: Radiotherapy dose escalation improves tumour control in prostate cancer but with increased toxicity. Boosting focal tumour only may allow dose escalation with acceptable toxicity. Intensity-modulated radiotherapy can deliver this, but visualization of the tumour remains limiting. CT or conventional MRI techniques are poor at localizing tumour, but dynamic contrast-enhanced MRI (DCE-MRI) may be superior. 18 patients with prostate cancer had T(2) weighted (T2W) and DCE-MRI prior to prostatectomy. The prostate wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 36 publications
3
70
1
Order By: Relevance
“…29) Also ZĂ€tterstrom et al followed a 55 year old male with cervical cystic dilatation and widened intrathoracic duct for 25 years without intervention. 15) In both of these cases the cysts underwent remission. Therefore while symptomatic lesions should be resected, it is better to simply follow up in asymptomatic patients with confirmed diagnosis over time.…”
Section: Discussionmentioning
confidence: 93%
“…29) Also ZĂ€tterstrom et al followed a 55 year old male with cervical cystic dilatation and widened intrathoracic duct for 25 years without intervention. 15) In both of these cases the cysts underwent remission. Therefore while symptomatic lesions should be resected, it is better to simply follow up in asymptomatic patients with confirmed diagnosis over time.…”
Section: Discussionmentioning
confidence: 93%
“…DCE takes advantage of the unique characteristics associated with the abnormal tumor vasculature to assess aggressiveness of the disease. The usefulness of DCE in detecting, localizing, and staging prostate cancer is well documented in literature [58,[86][87][88][89][90]. Additionally, several studies have reported promising findings on the utility of DCE parameters in discriminating prostate cancer based on aggressiveness of the disease [91,92].…”
Section: Dynamic Contrast-enhanced Imagingmentioning
confidence: 99%
“…The final approach to analyzing DCE images aims to estimate physiologically interpretable, kinetic parameters by fitting pharmacokinetic models to the enhancement curves [88,113,114]. The most common is the two-compartment model.…”
Section: Dynamic Contrast-enhanced Imagingmentioning
confidence: 99%
“…Research found that, for one radiologist using a commercial software, DCE-MRI resulted in superior tumour localization compared with T2W scans. They have demonstrated that tumours appear to have different enhancement property to benign peripheral zone and according to ROC analysis, this may results in a diagnostic test which would be considered of fairly discriminatory value by conventionally accepted criteria (17) . Sung Y.S et al studied the importance of computer-aided diagnosis for prostate carcinoma detection on dynamic contrast-enhanced MRI (DCE-MRI).…”
Section: Quantitative Approachmentioning
confidence: 99%